A 3D Printed Compact and Intelligent Power Module Based on Vibration Energy Harvester Integrated with Self‐Powered Triboelectric Sensor for Industry 4.0 IoT Applications. Issue 5 (17th October 2022) - Maharjan, Pukar; Lee, Sanghyun; Bhatta, Trilochan; Pradhan, Gagan Bahadur; Shrestha, Kumar; Jeong, Seonghoon; Rana, SM Sohel; Park, Jae Yeong
Abstract: In industry 4.0, continuous condition monitoring is essential to keep the system well maintained and stable. However, current monitoring systems demand periodic replacement/recharging of batteries. Herein, a compact vibration‐driven intelligent power module is proposed with excellent energy harvesting and self‐powered vibration sensing capability for industrial 4.0 IoT applications. By implementing newly designed 3D printed flat‐circular Z‐shaped springs, excellent performance is achieved from electromagnetic vibration energy harvester (VEH), whereas the integrated triboelectric‐based self‐powered vibration sensor (SVS) on springs is used for real‐time detection and monitoring of machinery vibration conditions simultaneously. VEH can deliver a maximum peak power of 1.95 W at 16 Hz and demonstrates excellent performance under a wide range (10‐100 Hz), whereas SVS exhibits an excellent vibration sensitivity (2.85 V Hz –1, 3.41 V s 2 m –1 ). The module is structurally and dimensionally like a standard D‐battery consisting of VEH, SVS, power management circuit (PMC), rechargeable Li‐Ion battery, and universal serial bus type‐c port (USB‐C). The module can sufficiently charge a built‐in battery from industry‐standard air‐pump motor and car engine vibrations such that the harvested energy from automobile engine vibration is successfully utilized to power multiple sensors (temperature, humidity, and pressure) and wireless transmission circuitries to realize a self‐powered smart wireless condition monitoring system. Abstract : A compact high‐performance intelligent power module equipped with a self‐powered vibration sensor is demonstrated for industry 4.0 IoT applications. The energy harvester generates excellent output power from the machinery vibrations along with wide frequencies which can be self‐stored for operating and processing the several sensor data for real‐time wireless condition monitoring for self‐powered industry 4.0 IoT applications.